Fertigation Strategies to Improve Water and Nitrogen Use Efficiency in Surface Irrigation System in the North China Plain - Xiulu Sun; Yizan Li; Marius Heinen; Henk Ritzema; Petra Hellegers; Jos van Dam (Agriculture, 2022)
Irrigation and fertilisation are often over-applied, which exceeds crop requirements. Surface fertigation, a technique of applying pre-dissolved fertilisers together with irrigation water, seems to be a viable way to improve the on-farm performance in the North China Plain (NCP). Thus, we conducted a field experiment based on farmers’ practices from 2017 to 2019. Moreover, we calibrated and validated SWAP-WOFOST-N, a seasonal integrated agro-hydrology and crop growth model, to assess the effects of different practices on yield, water and nitrogen use efficiency (WUE and NUE) and resource loss. Lastly, we developed various scenarios using the model to determine improved strategies. The results showed that the SWAP-WOFOST and extended Soil-N model offered satisfactory accuracy when compared with field measured data for the tested domain of the hydrological and nitrogen cycle; farmers’ current irrigation and fertilisation practices resulted in low WUE and NUE, but the practice of split top-dressing nitrogen did not show significant improvement in the surface irrigation system; WUE, NUE and nitrogen loss were closely related to irrigation practices. We further concluded that an optimised irrigation practice combined with an optimal fertigation scenario is the feasible strategy to achieve sustainable crop yield, high WUE and NUE and reduced nitrogen loss.